Om breve:Ni essays om brevformen i hverdagen, litteraturen og journalistikken - John Chr. Jørgensen (Museum Tusculanum Press, 2006)
The letter is the most widespread literary genre at all. For several hundred years letter books containing model letters for lovers have been published, while today they have been camouflaged as "manuals" for internet dating. John Chr. Jørgensen analyses the epistolary form in correspondences, epistolary novels and letters of travel through the past 150 years. En route the most recent - especially American - research in epistolary theory is presented and discussed. The book contains analyses of epistolary novels by M.A. Goldsmidt, Peter Nansen, Karin Michaëlis, Edith Rode, Sven Holm, Dea Trier Mørch, Iselin C. Hermann and Anders Bodelsen among others. The journalistic travelogue is traced from Herman Bang to Henrik Nordbrandt. The book is provided with a literary guide sorted out by subject, a subject index and an index of names.